2007
DOI: 10.1021/ic701233y
|View full text |Cite
|
Sign up to set email alerts
|

4-Amino- and 4-Nitrodipicolinatovanadium(V) Complexes and Their Hydroxylamido Derivatives:  Synthesis, Aqueous, and Solid-State Properties

Abstract: A number of 4-substituted, dipicolinatodioxovanadium(V) complexes and their hydroxylamido derivatives were synthesized to characterize the solid state and solution properties of five- and seven-coordinate vanadium(V) complexes. The X-ray crystal structures of Na[VO2dipic-NH2].2H2O (2) and K[VO2dipic-NO2] (3) show the vanadium adopting a distorted, trigonal-bipyramidal coordination environment similar to the parent coordination complex, [VO2dipic]- (1), reported previously as the Cs+ salt. The observed differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 58 publications
7
30
0
Order By: Relevance
“…Therefore, a comparison of the solid-state and solution chemical shifts is relevant; Table 2 contains selected δ iso values measured in aqueous solution. 13 Figure 9 shows a plot of solution vs. solid-state δ iso and reveals that the differences are all less than 30 ppm, likely due to solvent effects. It has been suggested that for vanadium complexes with weakly bound ligands, such as the H 2 O in these compounds, thermal and solvent effects are on the order of a few dozen ppm.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, a comparison of the solid-state and solution chemical shifts is relevant; Table 2 contains selected δ iso values measured in aqueous solution. 13 Figure 9 shows a plot of solution vs. solid-state δ iso and reveals that the differences are all less than 30 ppm, likely due to solvent effects. It has been suggested that for vanadium complexes with weakly bound ligands, such as the H 2 O in these compounds, thermal and solvent effects are on the order of a few dozen ppm.…”
Section: Discussionmentioning
confidence: 99%
“…The structures used in the calculations were obtained from single-crystal x-ray diffraction data 37,13 or the geometry optimized structure of VOCl 3 ; optimization was performed using B3LYP/6-311+G(d,p). Carbon-hydrogen bond lengths were set to 1.08 and 1.09 Å for carbons bonded to three and four other atoms, respectively.…”
Section: Computationsmentioning
confidence: 99%
See 3 more Smart Citations